174k views
5 votes
PLEASE HELP ASAP!!!! SUPER URGENT

PLEASE HELP ASAP!!!! SUPER URGENT-example-1
User BobRun
by
4.8k points

1 Answer

4 votes

Answer:

y = 2(x + 3)(x + 1)

Explanation:

Use the formula y = a(x-b)(x-c)

b and c are the x-intercepts

The x-intercepts in this function are -3 and -1

y = a(x+3)(x+1)

substitute the point (-2, -1)

-2 = a(-2 + 3)(-2 + 1)

-2 = a(1)(-1)

-2 = -a

a = 2

y = 2(x + 3)(x + 1)

User David Yates
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.